Analyzing the Performance of Ideological and Political Education in Universities: A Neutrosophic Approach to Handling Truth, Indeterminacy, and Falsehood in Students' Responses - Di Wangm (Neutrosophic Sets and Systems)
This paper presents a new way to evaluate ideological and political education (IPE) in universities using neutrosophic logic. Unlike traditional surveys that only show if students agree or disagree, this method looks deeper by also measuring how unsure students feel. Each answer is described using three values: truth (agreement), indeterminacy (uncertainty), and falsehood (disagreement). The model was tested in two different universities using a questionnaire that covered three areas: beliefs about national values, critical thinking, and civic behavior. The results showed that most students agreed with ideological ideas, but many were unsure when it came to critical thinking. A new tool called the Ideological Coherence Matrix (ICM), was also used to check if students were consistent in their views across different topics. Results showed that while many students were consistent, some had mixed or conflicting opinions. This highlights the need for better ways to connect ideas taught in class with how students actually think. The framework gives teachers and decision-makers a better understanding of student beliefs and helps improve how these topics are taught. We added another case study with ten criteria and six alternatives. This case study, we use the single valued neutrosophic set to overcome the uncertainty information. The single valued neutrosophic set is used with the EDAS method to rank the alternatives.